A case study of instructional time allocation of elementary schools in Taiwan and the USA. (1st January 2014) - Ortlieb, Evan; Chuang, Tao Wei
This study presents a comparison of the distribution of subject area courses across school days in two school districts: a US elementary school in South Texas and an elementary school in Taiwan. Grades one through five was included in the study. The data showed that the US school allocated much more time for language arts subjects. The elementary school in Taiwan addressed many more different subject areas in a day. The US school schedule reflected the primary goal of the school district, which was to improve reading skills. The Taiwan school scheduled reflected the goal of the school to provide a wide range of academic and real-life experiences for students.